2021
DOI: 10.1002/cpe.6201
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, simulation, and case analysis of COVID‐19 over network public opinion formation with individual internal factors and external information characteristics

Abstract: With the development of information technology, the Internet has become an important channel of public opinion for expressing public interests, emotion, and ideas. Public emergency usually spreads via network. Due to the temporal and spatial flexibility and the information amplification of network, the opinions from different regions and background are easy to be represented as network public opinion, and have important impact on social and economic life. Thus, studying the formation mechanism of network publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…How to interoperate between heterogeneous knowledge bases has become a main problem in the current information management department that needs to be solved by domestic and foreign scholars. It has become one of the main problems that domestic and foreign scholars need to solve that the relevant government departments provide crossplatform, cross-system knowledge association, analysis, and text mining [1,2]. e interoperation of different types of public opinion knowledge base groups has become the main means to complete the crossover and integration of multimedia public opinion data information under big data [3,4], and it has also become an effective means for the acquisition, preservation, and use of big data information for multimedia network public opinion [5].…”
Section: Introductionmentioning
confidence: 99%
“…How to interoperate between heterogeneous knowledge bases has become a main problem in the current information management department that needs to be solved by domestic and foreign scholars. It has become one of the main problems that domestic and foreign scholars need to solve that the relevant government departments provide crossplatform, cross-system knowledge association, analysis, and text mining [1,2]. e interoperation of different types of public opinion knowledge base groups has become the main means to complete the crossover and integration of multimedia public opinion data information under big data [3,4], and it has also become an effective means for the acquisition, preservation, and use of big data information for multimedia network public opinion [5].…”
Section: Introductionmentioning
confidence: 99%
“…This was demonstrated in [59] for the climate change topic and the topic of public opinion about police funding [64] at around the time of the murder of George 7 Human Behavior and Emerging Technologies Floyd at the hands of law enforcement in the United States [155]. It was also seen that the level of a person's stubbornness was shown to be inversely correlated to the probability of belief change [55]. The hypothesized correlation between emotional arousal and polarization was confirmed.…”
Section: Domain-specific Dimension As Shown In Tablementioning
confidence: 78%
“…Through the literature review on the influencing factors and propagation rules of online public opinion, it was found that the research on the influencing factors of new coronavirus online public opinion is mostly concentrated in computer science and other fields. These studies usually analyze online public opinions from the perspective of data modeling [ 25 , 26 , 27 ]. At present, there is a lack of systematic identification and risk interaction research on risk factors of COVID-19, and the research on risk transmission mechanism of online public opinion of COVID-19 is relatively insufficient.…”
Section: Literature Reviewmentioning
confidence: 99%